Contrarian Investment Strategy: a Superior Active portfolio approach - Faez Hasan, Mohammed; Ahmed Faris, Ali; Abdulkadir Abdulsatar, Nada (Iraqi Journal for Administrative Sciences, 2024)
Amongst the foreseen well-known investment strategies, this study tries to test the validity of forming a superior active portfolio based on a contrarian investment strategy. To reach this aim, we have been using monthly stock’s close prices of 37 listed-companies in the Iraq stock exchange (ISX) as sample, which was to extend throughout the period between January 2005 to January 2015. The applied method regards to forming an Active portfolio that outperforms the market-index portfolio according to paradoxical expectations for the market performance by using 49 mixed strategies for ranking and holding periods. The principle of forming the Contrarian active portfolio is based on buying the lose stocks in the previous period and selling the winners for that same period, this mechanism iterated to generate return that called contrary return. The produced return tested under statistical and economical significancy in the same time. The major finding is that contrarian returns (After transaction cost) appears in the short-term for Iraq stocks exchange.